Standard electroencephalography in clinical psychiatry : a practical handbook - Boutros, Nashaat N. (Chichester, West Sussex Hoboken, NJ Wiley-Blackwell, 2011)
"This book provides a concise overview of the possible clinical applications of standard EEG in clinical psychiatry. It starts with a short history then describes the physiologic basis of the EEG signal. The material is clearly presented throughout, with figures, tables with summaries of relevant findings, flow diagrams for diagnostic work-up, boxes with learning points, and short lists of key references"--
Keywords: Electroencephalography; Mental illness; MEDICAL / Psychiatry / General